Application of inverter input rating method and standard AC voltage drop/over method on automatic transfer switch for hybrid powered e-bike charging station - Hidayat, Mohammad Noor; Imammuddin, Azam Muzakhim; Munir, Abdullah Faiq; Nugroho, Aji (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
Automatic transfer switch (ATS) is useful for integrating two different energy sources can be applied to e-bike charging stations. Renewable energy sources from sunlight using 2×100 Wp photovoltaic (PV) modules as the main source in this study, as well as grid energy sources functioned as backup energy. This ATS uses inverter input rating methods and standard AC voltage drop/over, a novelty of this study. The amount of current during testing is up to 14.09 A. The value of the inverter input voltage affects the quality of the inverter output voltage, there is a stability of the inverter output voltage from the AC voltage standard ±5% of the, lowest voltage value of (Vo_inv) = 223.9 V and the highest value (Vo_inv) = 226.1 V, at the time of (Vi_inv) max = 14.15 V and (Vi_inv) min = 12.66 V. It can be concluded that the ATS works in the PV position of the supply to the e-bike load, in the PV state it can produce power of a maximum value of 135.9 W at 11:25 am and is at the lowest power of 31 W at 03:31 pm. This ATS device in the switch mode successfully implemented a duration range of 10-21 ms, during the transfer of energy.